Death: An Evolving, Normative Concept - Caplan, Arthur (The Hastings Center report, 2018)
Constantin Reliu had been working for twenty years as a cook in Turkey when he returned to his hometown of Barlad, Romania, to discover that, there, he was dead. His former wife had, unbeknownst to him, at some point during his stay in Turkey registered him as deceased in Romania. He has since been living a legal nightmare trying to prove to Romanian authorities that he is, in fact, alive. Reliu is not alone in finding out that the legal system is not as attuned to physiological activity or biological assessment by doctors in determining death as one might think. If one starts with the assumption that death is a purely biological concept, solely the province of doctors, Reliu's story seems entirely unrelated to the concept of death in the medical context. A brain scan would not lead to a reversal of his being assessed as dead. The story is a reminder, however, that how death is used is not just biological, and therefore that the standard of death even in the clinic must answer to cultural considerations. Values, the law, and custom matter a great deal in determining who is alive and who is not, whether in the courtroom, the coroner's office, or the clinic.